Writing for publication in nursing and healthcare : getting it right - Holland, Karen, 1949-; Watson, Roger, 1955- (Chichester, West Sussex : Wiley-Blackwell, 2012)
Writing for Publication in Nursing and Healthcare is an invaluable guide to'getting it right', focusing on all aspects of writing for publication. It will help the reader to develop skills in writing articles, book reviews and other forms of publications, and can also be used as an aide-memoir for editors and journal/book reviewers. It explores:How to get startedHow to write various forms of publication including abstracts, papers, book reviews, journal articles and booksGood practice in reviewingThe editorial processEthical and legal aspects of publishing Offering guidance, tips, examples an.
Introduction : the book, its philosophy and its focus / Karen Holland and Roger Watson -- The basics of writing for publication and the steps to success : getting started / Roger Watson -- Writing a conference abstract and paper / Jan Draper -- Writing for publication : the book review / Dean Whitehead -- Writing for publication : the journal article / Roger Watson -- Writing for publication : the book / Karen Holland -- Writing for publication : the essential literature review / Zena Moore -- Writing for publication : turning assignments into publishable work / Mark Hayter -- Writing for publication : turning the conference paper into publishable work / Tracy Levett-Jones and Teresa Stone -- The editorial process / Roger Watson -- Being a journal reviewer : good practice in reviewing / Karen Holland -- Ethical and legal aspects of publishing : avoiding plagiarism and other issues / Charon A. Pierson -- The World Wide Web and its potential for publication / Paul Murphy and Seamus Cowman -- Dissemination of published work : the process and the value / Sue Turale -- Other forms of writing: letters, commentaries, and editorials / David R. Thompson and Chantal F. Ski -- Where do we go from here? : action planning for writing and publishing / Roger Watson and Karen Holland.
Includes bibliographical references and index.
Print version record.
Keywords: Nursing -- Authorship; Nursing literature -- Marketing; Writing; Publishing; Nurses' Instruction; Electronic books